Phase Ib of Sorafenib in Combination With Everolimus in Patients With Advanced Solid Tumors, Selected on the Basis of Molecular Targets. (27th March 2014) - Toffalorio, Francesca; Spitaleri, Gianluca; Catania, Chiara; Dal Zotto, Laura; Noberasco, Cristina; Delmonte, Angelo; Santarpia, Mariacarmela; Vecchio, Fabio; Brunelli, Veronica; Rampinelli, Cristiano; Barberis, Massimo; Fumagalli, Caterina; et al.
Abstract: Background: Molecular alterations of the PI3K and Ras pathways often occur in human cancer. In this trial, the pharmacokinetics, toxicity, and activity of two drugs inhibiting these pathways—everolimus and sorafenib—were investigated. Methods: Thirteen patients with progressing solid tumors were treated with everolimus and sorafenib, according to a 3+3 scheme. Patients were selected on the basis of immunohistochemical expression of tumor molecular targets, including phospho‐AKT, ‐p70S6K, and ‐ERK1/2. Results: The daily recommended dose identified was 2.5 mg of everolimus and 600 mg of sorafenib. Dose‐limiting toxicities included grade 3 asthenia and hand‐foot skin reaction. No grade 4 adverse events were observed. The most frequent grade 3 toxicities were hypophosphatemia (30.8%), alanine aminotransferase level increase, asthenia, and anorexia (14%). No pharmacokinetic interactions were identified between everolimus and sorafenib. Of 12 evaluable patients, we observed 2 partial responses, with greater than 10% shrinkage in an additional 5 patients. Objective responses were observed in one patient with a thymoma and in one patient with a lung adenocarcinoma. Tumor shrinkage that did not qualify as a partial response was seen in an abdominal leiomyosarcoma and in adenoid cystic carcinomas. Conclusion: The combination of everolimus and sorafenib is safe. The tumor activity observed in different tumor types could be the result of the combined action of these drugs as well as the molecular selection of the treated population. Further research is warranted to better investigate drugs simultaneously blocking the PI3K and the Ras pathways and to refine patient selection. Abstract : 摘要 背景 . 人类癌症中常出现PI3K和Ras通路的分子改变。本试验探索了两种靶向这些通路的药物——依维莫司和索拉非尼——的药物代谢动力学（PK）、毒性反应以及活性。 方法 . 13例实体瘤进展的患者按3+3方案接受了依维莫司和索拉非尼治疗。患者根据肿瘤分子靶点的免疫组化结果进行选择，包括磷酸化AKT、磷酸化p70S6K以及磷酸化ERK1/2。 结果 . 依维莫司每日推荐剂量为2.5 mg，索拉非尼为600 mg。剂量限制性毒性反应包括3级虚弱和手足皮肤反应。未观察到4级不良事件。最常见的3级毒性反应为低磷血症（30.8%）、丙氨酸氨基转移酶水平升高、虚弱以及厌食（14%）。依维莫司与索拉非尼之间未发现PK方面的相互作用。12例可评估患者中，2例达到部分缓解，另5例患者肿瘤缩小10%以上。客观缓解见于1例胸腺瘤和1例肺腺癌患者。肿瘤缩小但未达部分缓解标准的情况见于1例腹部平滑肌肉瘤和1例腺样囊性癌患者。 结论 . 依维莫司和索拉非尼联合方案是安全的。不同肿瘤类型中均观察到抗肿瘤活性，这源于药物的联合作用以及对治疗人群的分子选择。需要进一步研究来更好地探索能够同时阻断PI3K和Ras通路的药物，以及更精准地选择患者。 The Oncologist 2014;19:344‐345